Capturing a novel metastable polymorph of the anticancer drug gefitinib - Thorat, Shridhar H.; Patwadkar, Manjusha V.; Gonnade, Rajesh G.; Vaidhyanathan, R. (CrystEngComm, 2014)
Gefitinib, a life-extending anticancer drug, exhibits solvent-mediated conformational polymorphism to yield stable (form I) and novel metastable (form II) polymorphs. Crystal structure analysis revealed 3D isostructurality in the molecular organization of the polymorphs, and the metastable polymorph undergoes a crystal-to-crystal thermal phase transition to the stable polymorph.